Zero-Trust Architectures: Redefining Enterprise Security Models (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
: The traditional perimeter-based security model has become inadequate in the face of increasing cyber threats, cloud adoption, remote work, and complex enterprise environments. Zero-Trust Architecture (ZTA) emerges as a transformative security paradigm that challenges the conventional “trust but verify” approach by enforcing strict identity verification, least-privilege access, and continuous monitoring regardless of user location or network origin. This paper explores how ZTA fundamentally redefines enterprise security by eliminating implicit trust and adopting a “never trust, always verify” stance. We analyze key components of zero-trust models, including micro-segmentation, identity and access management (IAM), multi-factor authentication (MFA), and real-time analytics for threat detection. Our research synthesizes recent advancements in zero-trust frameworks and evaluates their effectiveness in mitigating insider threats, lateral movement, and supply chain attacks within hybrid cloud and on-premises infrastructures. The study further proposes a comprehensive zero-trust implementation framework tailored for enterprises seeking to enhance resilience against evolving threats while maintaining operational agility. Through case studies and simulation scenarios, we demonstrate that zero-trust adoption significantly reduces attack surfaces and breach impact. Challenges related to organizational change management, technology integration, and scalability are also discussed. Finally, we identify future research directions such as AI-enhanced zero-trust policies, automated trust evaluation, and integration with emerging technologies like 5G and edge computing. Our findings underscore the imperative for enterprises to transition toward zero-trust models to secure dynamic IT landscapes effectively.
Keywords: Zero-Trust Architecture; Enterprise Security; Identity and Access Management; Micro-Segmentation; Multi-Factor Authentication; Cybersecurity; Hybrid Cloud Security; Insider Threats; Threat Detection; 2024 Security Trends